Återkopplingens roll vid balanserad styrning : En studie av en kommunal förvaltning - Brandorf, Per; Hultin, Daniel (2014)
The management in the public sector has recently become more similar to the private sector. One important reason is an increased demand for quality and cost effectiveness. An example of this is when public organizations adopt the private sectors models for balanced management. This study investigates how a public organization relates and works with feedback during balanced management. The purpose is to identify how feedback can contribute to an appropriate use of a balanced management model in a public organization. The study is based on theories about feedback and balanced management combined with a case study of the technical department at the municipality of Luleå. The department uses a balanced scorecard. The result of the study reveals an agreement of the importance of feedback in the management work. However, targets that are not perceived as relevant and time consuming procedures to report feedback tends to decrease the incentives to work with feedback. If there is an absence or a low quality of reported feedback there is a risk that the organization will not be able to use feedback to support the work with the balanced scorecard. The public sector is involved in many different areas and the operative work is often service related. This matter makes it difficult to create relevant and measurable targets. This makes it difficult to use a balanced management model in a public organization. To suggest a solution, this study concludes in a model for how feedback can contribute to an appropriate use of a balanced management model in a public organization. Validerat; 20141217 (global_studentproject_submitter)